Effects of Nebivolol and Telmisartan on Blood Pressure, Diastolic Functions, Lipid and Glucose Metabolism in Hypertensive Cases - Daglı, Necati; Karaca, İlgın (Fırat University, 2006)
Objectives: Nebivolol and Telmisartan has been claimed to ensure effective control of the blood pressure and target organ. The aim of our study was to investigate the effects of nebivolol and telmisartan on glucose-lipid metabolism, as well as diastolic dysfunction and left ventricle hypertrophy, which are held responsible for target organ damage. Materials and Methods: The study enrolled 100 patients whose mean age was 50.1 ± 9.9 and who had essential hypertension (50 patients were administered 5 mg/day Nebivolol and 50 patients were administered 80 mg/day Telmisartan for six months). Results: Mean blood pressure fell from 108.1±9.6 mmHg to 88.8±6.8 mmHg in the nebivolol group (p=0.001) and from 108.8±2.2 mmHg to 95.3±3.5 mmHg in the telmisartan group (p=0.001). Insulin resistance changed from 3.27±2.15 to 3.72±2.02 in the nebivolol group (p=0.13) and from 2.56±1.3 to 2.72±1.52 in the telmisartan group (p>0.05). Echocardiography showed a decrease in the left ventricle mass indices (p

Amaç: Nebivolol ve Telmisartan etkin kan basıncı kontrolü sağlar ve hedef organ hasarı üzerine olumlu etkileri vardır. Çalışmamızın amacı nebivolol ve telmisartanın glükoz-lipid metabolizması üzerine ve hedef organ hasarından sorumlu tutulan diyastolik disfonksiyon ve sol ventrikül hipertrofisi (SVH) üzerine olan etkilerini irdelemek idi. Gereç ve Yöntem: Çalışmaya yaş ortalaması 50.1±9.9 olan esansiyel hipertansiyonlu 100 hasta alındı. Elli hastaya Nebivolol 5 mg/gün, diğer 50 hastaya ise Telmisratan 80mg/gün altı ay süre ile verildi. Bulgular: Ortalama kan basıncı nebivolol grubunda 108.1±9.6 mmHg'dan 88.8±6.8 mmHg'a (p=0.001), telmisartan grubunda ise, 108.8±2.2 mmHg'dan 95.3±3.5 mmHg'a geriledi (p=0.001). İnsülin direncinde nebivolol grubunda 3.27±2.15'den 3.72±2.02'ye (p=0.13) telmisartan grubunda ise 2.56±1.3'den 2.72±1.52'ye değişim tespit ettik (p>0.05). Ekokardiyografik olarak her iki grupta da sol ventrikül kitle indekslerinde azalma (p
Hipertansif Olgularda Nebivolol ve Telmisartan'ın Kan Basıncı, Diyastolik Fonksiyonlar, Lipid ve Glukoz Metabolizması Üzerine Etkileri